Constraints on emissions of carbon monoxide, methane, and a suite of hydrocarbons in the Colorado Front Range using observations of 14CO2 - B. W. LaFranchi; G. Pétron; J. B. Miller; S. J. Lehman; A. E. Andrews; E. J. Dlugokencky; B. Hall; B. R. Miller; S. A. Montzka; W. Neff; P. C. Novelli; C. Sweeney; et al. (Atmospheric Chemistry and Physics, 2013)
Atmospheric radiocarbon (14C) represents an important observational constraint on emissions of fossil-fuel derived carbon into the atmosphere due to the absence of 14C in fossil fuel reservoirs. The high sensitivity and precision that accelerator mass spectrometry (AMS) affords in atmospheric 14C analysis has greatly increased the potential for using such measurements to evaluate bottom-up emissions inventories of fossil fuel CO2 (CO2ff), as well as those for other co-emitted species. Here we use observations of 14CO2 and a series of primary hydrocarbons and combustion tracers from discrete air samples collected between June 2009 and September 2010 at the National Oceanic and Atmospheric Administration Boulder Atmospheric Observatory (BAO; Lat: 40.050° N, Lon: 105.004° W) to derive emission ratios of each species with respect to CO2ff. The BAO tower is situated at the boundary of the Denver metropolitan area to the south and a large industrial and agricultural region to the north and east, making it an ideal location to study the contrasting mix of emissions from the activities in each region. The species considered in this analysis are carbon monoxide (CO), methane (CH4), acetylene (C2H2), benzene (C6H6), and C3–C5 alkanes. We estimate emissions for a subset of these species by using the Vulcan high resolution CO2ff emission data product as a reference. We find that CO is overestimated in the 2008 National Emissions Inventory (NEI08) by a factor of ~2. A close evaluation of the inventory suggests that the ratio of CO emitted per unit fuel burned from on-road gasoline vehicles is likely over-estimated by a factor of 2.5. Using a wind-directional analysis of the data, we find enhanced concentrations of CH4, relative to CO2ff, in air influenced by emissions to the north and east of the BAO tower when compared to air influenced by emissions in the Denver metro region to the south. Along with enhanced CH4, the strongest enhancements of the C3–C5 alkanes are also found in the north and east wind sector, suggesting that both the alkane and CH4 enhancements are sourced from oil and gas fields located to the northeast, though it was not possible to rule out the contribution of non oil and gas CH4 sources.